Pemphigoid gestationis: current perspectives - Sävervall C; Sand FL; Thomsen SF (Dove Medical Press, 2017)
Christine Sävervall,1 Freja Lærke Sand,1 Simon Francis Thomsen1,2 1Department of Dermatology, Bispebjerg Hospital, Copenhagen, Denmark; 2Department of Biomedical Sciences, University of Copenhagen, Copenhagen, Denmark Abstract: Many skin diseases can occur in pregnant women. However, a few pruritic dermatological conditions are unique to pregnancy, including pemphigoid gestationis (PG). As PG is associated with severe morbidity for pregnant women and carries fetal risks, it is important for the clinician to quickly recognize this disease and refer it for dermatological evaluation and treatment. Herein, we review the pathogenesis, clinical characteristics, and management of PG. Keywords: pemphigoid gestationis, pregnancy, skin diseases